2018
DOI: 10.1007/s12149-018-1253-0
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity in 18F-FDG PET/CT by textural analysis in breast cancer as a predictive and prognostic subrogate

Abstract: Textural variables obtained with F-FDG PET/CT were predictors of neoadjuvant chemotherapy response and prognosis, being as relevant as PET stage at diagnosis for OS and DFS prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 43 publications
2
25
0
2
Order By: Relevance
“…This feature was mainly found in oncology research (61)(62)(63)(64). For example, a study on breast cancer showed that LRHGE was associated with risk categories as well as the neoadjuvant chemotherapy response (61). Another study on cervical cancer found that LRHGE was correlated with the differentiation (62).…”
Section: A B Cmentioning
confidence: 94%
“…This feature was mainly found in oncology research (61)(62)(63)(64). For example, a study on breast cancer showed that LRHGE was associated with risk categories as well as the neoadjuvant chemotherapy response (61). Another study on cervical cancer found that LRHGE was correlated with the differentiation (62).…”
Section: A B Cmentioning
confidence: 94%
“…Similar to breast density in mammography, background parenchymal enhancement and background parenchymal uptake may be regarded as potential imaging biomarkers for breast cancer incidence [85]. Texture analysis and radiomics could also play a role in the evaluation of tumor aggressiveness as well in the prediction of response to neoadjuvant chemotherapy [86][87][88]. However, only few single center studies are available on PET MRI-derived imaging biomarkers for local breast cancer staging.…”
Section: Local Stagingmentioning
confidence: 99%
“…Non-invasive image-derived biomarkers can also be generated from PET radiomics according to the intensity of the pixels, their associated parameters, and their positions ( 138 ). Based on the clinical application of PET-based techniques, several studies have focused on the clinical and technical feasibility of applying PET radiomics to diagnosis ( 139 , 140 ), staging ( 141 143 ), pathological characterization ( 17 , 18 ), NAC response ( 18 , 144 146 ), and outcome prediction ( 147 , 148 ) in breast cancer. However, the difficulty in detecting the edges of breast lesions using CT limits the PET/CT in identifying the breast tumor and the alignment of the imaging modalities ( 141 ).…”
Section: Recent Advances In Pet-based Strategiesmentioning
confidence: 99%